Current state of management of struma ovarii and preoperative imaging features: A retrospective case series study of 18 patients at a single institution. Issue 3 (11th January 2023) - Tamura, Nami; Murakami, Keisuke; Ozaki, Rie; Takeuchi, Shiori; Ochiai, Asako; Kawasaki, Yu; Okada, Yukiko; Kitade, Mari; Itakura, Atsuo
Abstract: Aim: Even though 95% of struma ovarii are benign, it is often overtreated because of the difficulty to distinguish it from malignancy. In this study, our aim was to evaluate the current state of the preoperative diagnosis and the selection of the surgical procedure, and to improve preoperative diagnostic accuracy by retrospectively reviewing imaging findings. Methods: We retrospectively reviewed the clinical course and imaging characteristics of 18 patients who were diagnosed postoperatively with struma ovarii, pathologically, at our institution between 2015 and 2021. Results: The preoperative diagnoses included benign ovarian tumor in eight cases, borderline in four cases, and malignant in six cases. None of the cases were diagnosed as struma ovarii preoperatively. Of the seven patients who had confirmed a desire for future childbearing, four patients were suspected for borderline or malignant tumor preoperatively, and underwent abdominal adnexectomy. In patients without a desire for childbearing, laparoscopic surgery was performed in only 45% of the patients whose preoperative diagnosis was benign. On magnetic resonance imaging (MRI), 54% of the cases showed enhanced solid components, which is characteristic of malignant tumors, but diffusion restriction was observed in only 11%. On computed tomography (CT), 78% of the cases showed a high attenuation lesion reflecting thyroid tissue. Conclusions: Struma ovarii is difficult to distinguish from malignancy preoperatively, making the choice of surgical approach complicated. A comprehensive evaluation of diffusion‐weighted MRI and CT findings may improve the accuracy of preoperative diagnosis of struma ovarii.